Characteristics of Lower Extremity Infection Rates Following Mohs Micrographic Surgery. Issue 12 (December 2021) - Niklinska, Eva B.; Hicks, Alexander; Wheless, Lee; Hanlon, Allison
Abstract : BACKGROUND: Surgical site infection (SSI) is the most common complication for Mohs micrographic surgery (MMS). Lower extremity surgical sites are at an increased risk for developing SSI. OBJECTIVE: This study aimed to evaluate lower extremity SSI rates post-MMS based on closure type and antibiotic usage. MATERIALS AND METHODS: A retrospective review was performed of all lower extremity MMS cases from 2011 to 2016 at Vanderbilt University Medical Center. Patient history, surgical details, and follow-up appointments were reviewed. RESULTS: Six hundred twenty MMS lower extremity surgeries were eligible. Review identified an overall lower extremity SSI rate of 7.4%. Infection rates were significantly increased in wound closed by flaps/grafts ( p < .001). Although wound size and preoperative antibiotic prophylaxis were initially associated with increased infection rate ( p = .03, p = .015), the associations were fully attenuated when adjusting for closure type. CONCLUSION: More complicated repair techniques (flap/graft) for larger wound sizes contribute to increased SSI risk among lower extremity MMS cases. Providers can use this information to guide antibiotic prophylaxis.